Landscape approaches to achieving food production, natural resource conservation, and the Millennium Development Goals. - Milder, Jeffrey C.; Buck, Louise E.; DeClerck, Fabrice A.J.; Scherr, Sara J. (Springer, 2012)
The Rio Copan watershed in western Honduras is not unlike many agricultural landscapes throughout the developing world. A journey through this 800 km2 watershed reveals a mixture of small and mid-sized farms producing cattle, coffee, and subsistence crops. Residents here face many challenges: recent population growth has led to deforestation and water pollution, while agricultural productivity is generally low and poverty levels remain high, especially among the indigenous Mayan population.